Peruvian Tenebrionidae: A Review of Present Knowledge and Biodiversity - Giraldo, Alfredo E. (2016)
A review of several aspects dealing with Tenebrionidae in Peru is presented. The study includes a taxonomic history, depositories of type specimens, taxonomic diversity, endemicity, ecological studies, and other research involving Peruvian tenebrionids in medicine, agriculture, food protection and production. Analyses of the geographic distribution, habitats and estimation of the species richness are performed. A final recommendation suggesting the development of four main lines of research on Peruvian tenebrionids is presented, including: 1) systematics and biogeography, 2) spatial and temporal patterns of epigaeic assemblages, 3) morphological adaptations to aridity, and 4) preserving material of some representatives of Peruvian taxa for molecular studies.